2016
DOI: 10.1002/jbm.a.35720
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine fibronectin from differentiating mesenchymal stem cells induces the neurite elongationin vitroand promotes nerve fiber regeneration in transected spinal cord injury

Abstract: Extracellular matrix (ECM) expression is temporally and spatially regulated during the development of stem cells. We reported previously that fibronectin (FN) secreted by bone marrow mesenchymal stem cells (MSCs) was deposited on the surface of gelatin sponge (GS) soon after culture. In this study, we aimed to assess the function of accumulated FN on neuronal differentiating MSCs as induced by Schwann cells (SCs) in three dimensional transwell co‐culture system. The expression pattern and amount of FN of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 69 publications
(122 reference statements)
0
21
0
Order By: Relevance
“…Fibronectin is a crucial component of the extracellular matrix (ECM) and is involved in epithelial-mesenchymal transition [74]. Moreover, MSCs can secrete fibronectin [75] promoting neurite elongation of MSCs after neural induction [76]. The obtained qRT-PCR results of hWJ-NSCs were compared to undifferentiated cells (hWJ-MSCs).…”
Section: Quantitative Reverse Transcription Polymerase Chain Reactionmentioning
confidence: 99%
“…Fibronectin is a crucial component of the extracellular matrix (ECM) and is involved in epithelial-mesenchymal transition [74]. Moreover, MSCs can secrete fibronectin [75] promoting neurite elongation of MSCs after neural induction [76]. The obtained qRT-PCR results of hWJ-NSCs were compared to undifferentiated cells (hWJ-MSCs).…”
Section: Quantitative Reverse Transcription Polymerase Chain Reactionmentioning
confidence: 99%
“…MSC‐derived exosomes have also been tested in porcine model of TBI coupled with hemorrhagic shock; consistent with the rodent data, the pigs had fewer cognitive deficits as determined with a neurological severity score and recovered faster than nontreated pigs . There is also evidence for MSC inducing immune suppression and anti‐inflammation; stimulating neurogenesis and angiogenesis; activating survival pathways and inhibiting apoptotic pathways; and enhancing neuroplasticity through neurite outgrowth and synaptogenesis …”
Section: Cell Therapy In Tbimentioning
confidence: 54%
“…It has been suggested that the combined use of tenascincytotactin, nerve growth factor /brain-derived neurotrophic factor/retinoic acid and human bone marrow-derived multipotent progenitor cells offers a new feasible method for nerve repair [134]. Fibronectin secreted by mesenchymal stem cells in the early stage has been found to accumulate on gelatin sponge scaffolds and promote neurite elongation of neuronal differentiating mesenchymal stem cells as well as nerve fiber regeneration after spinal cord injury [135].…”
Section: Measures To Increase the Efficiency Of Bone Marrow Mesenchymmentioning
confidence: 99%